The Influence of Corporate Social Responsibility (CSR) on Company Value with Profitability as a moderating variable (In Tobacco Subsector Companies Listed on the IDX in 2018-2023) - Novia, Hana; Prima Jaya, Fanlia (PT. Hanken Sukses Jaya, 2025)
The aim of this research is to determine whether CSR affect firm value ang profitability, and whether CSR impact firm value through profitability. CSR disclosure is measured based on the Global Reporting Intiative (GRI) version 4, which is divided into three categories: economic, environmental and social, and is proxied in the Corporate Social Responsibility Disclosure Index (CSRDI). Firm value is measured using financial ratios such as Tobin’s Q ratio and Price Book Value (PBV) ratio. Profitability is proxied by Return On Assets (ROA) and Return On Equity (ROE). The population of this research are all of tobacco sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2018-2023. The sample for this research is selected using purposive sampling technique, with a total sample of 3 companies and 72 data points. This research using Partial Least Square (PLS) data analysis model with t-test, assisted by SmartPLS software. The result of this research demonstrate that CSR has a signiricant impact on firm value, CSR significally influence profitability and CSR significantly affects firm value through profitability